Exploring Determinant Factors of Differences Between Governmental Accounting And National Accounts Budgetary Balances in EU Member States - Susana Margarida JORGE; Maria Antonia JORGE DE JESUS; Raul M.S. LAUREANO (Transylvanian Review of Administrative Sciences, 2014)
Framed by the earnings management ap-proach, this paper addresses the relationship be-tween budgetary balances according to Govern-mental Accounting (GA) and National Accounts (NA), exploring factors that may explain both the materiality and diversity of the adjustments required when translating data from one into the other. Using data from Excessive Defcits Proce-dure reporting for all EU member states from 2007 to 2010, the analysis confrms that GA-NA adjustments refect conceptual differences be-tween the two systems, namely concerning rec-ognition criteria. Regarding potential factors ex-plaining adjustments, while none of the economic policy variables considered was found relevant in explaining either diversity or materiality, all tech-nical accounting variables analyzed explained materiality, although only GA accounting basis explained diversity.The research shows that changing GA re-porting basis into accruals reduces adjustments’ materiality and diversity. Therefore, in order to improve the quality of Government Finance Statistics (GFS), it is highly recommendable to achieve a GA system harmonized across Eu-rope, such as IPSASs or EPSASs, allowing only very few options and imposing the accrual basis in both budgetary and fnancial systems. Also relevant is the need to strengthen the role of con-trol and auditing in the GA reporting process (by Supreme Audit Institutions and external private frms), in order to avoid accounting discretion.